Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Answer:
[tex]x + y + 2 = 0- - - eqn(i) \\ x - y - 1 = 0 - - - eqn(ii) \\ eqn(i) + eqn(ii) \\ = 2x + 1 = 0 \\ 2x = -1 \\ x = - \frac{1}{2} \\ substitute \: for \: x \: in \: eqn(i) \\ -\frac{1}{2} + y + 2 = 0 \\ y = (-2 + \frac{1}{2} ) \\ y = -\frac{3}{2} [/tex]
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.